Casa Familiar Rural (CFR) na Amazônia Paraense: uma análise da agricultura sustentável nas comunidades de Membeca, Vila Amazonas e Guajará. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The Lago Grande region, located in the municipality of Santarém in the state of Pará, is characterized by its natural wealth and the presence of rural communities that rely on family farming as their main means of subsistence. However, the Amazon region of Pará has been facing continuous exploitation of natural resources and the implementation of large capitalist projects, forcing rural residents to reinvent themselves and learn new alternative farming techniques that allow them to work the land while respecting nature and their traditional knowledge. In this context, Rural Education is centered on addressing the socioeconomic, cultural, and environmental realities. By connecting the community’s lived experiences with theoretical knowledge, students are encouraged to apply practical skills on their farms, promoting agricultural alternatives that preserve nature and improve the quality of life for families. This study aims to analyze the contribution of Alternating Pedagogy to agricultural sustainability in the Amazon region of Pará, with an emphasis on agroecology, focusing specifically on the communities of Membeca, Vila Amazonas, and Guajará.Students from the agroecology program at the Rural Family House (CFR) engage in hands-on activities during the "community time" through the pedagogical tool known as the Young Professional Project (PPJ). These activities include meliponiculture, Agroforestry Systems (AFS), local poultry farming, rotational grazing management, and more. Therefore, this work comprises a literature review and field research using both qualitative and quantitative approaches, including photographic records of students’ production units and interviews with the students, technical teachers, the CFR coordinator, and representatives from the Regional Association of Rural Family Houses (Arcafar).The analysis of these experiences aims to support the strengthening of rural communities by identifying the challenges faced in implementing agroecological farming practices that promote the diversification of family farming production, generating income and well-being for those living in rural areas. This highlights opportunities to improve the formulation of public policies.
Keywords: Sustentabilidade Agrícola; Diversificação da produção; Políticas públicas; Pedagogia da Alternância; Casa Familiar Rural; CNPQ:: CIÊNCIAS HUMANAS; Políticas Públicas e Estratégias de Desenvolvimento Regional